Transient Interactions of a Cytosolic Protein with Macromolecular and Vesicular Cosolutes: Unspecific and Specific Effects. Issue 18 (6th November 2015) - Ceccon, Alberto; Busato, Mirko; Pérez Santero, Silvia; D'Onofrio, Mariapina; Musiani, Francesco; Giorgetti, Alejandro; Assfalg, Michael
Abstract: Cytosolic proteins do not occur as isolated but are exposed to many interactions within a crowded cellular environment. We investigated the associations between a test cytosolic protein, human ileal bile acid binding protein (IBABP), and model cosolutes mimicking macromolecular and lipid membrane intracellular components. Using fluorescence spectroscopy, heteronuclear NMR, and molecular dynamics, we found that IBABP associated weakly with anionic lipid vesicles and experienced transient unspecific contacts with albumin. Localized dynamic perturbations were observed even in the case of apparent unspecific binding. IBABP and ubiquitin did not display mutually attractive forces, whereas IBABP associated specifically with lysozyme. A structural model of the IBABP–lysozyme complex was obtained by data‐driven docking simulation. Presumably, all the interactions shown here contribute to modulating functional communication of a protein in its native environment. Abstract : Leave me alone ! Proteins in native environments are never isolated. We show here, by biochemical and computational methods, that the test protein human ileal bile acid binding protein engages in both unspecific and specific ultraweak interactions with model intracellular components.